2019
DOI: 10.1177/1532440019851806
|View full text |Cite
|
Sign up to set email alerts
|

Federalism, Government Liberalism, and Union Weakness in America

Abstract: Unlike most other countries, in the United States, subnational governments (states) have substantial authority over collective bargaining and union organization laws. Because states compete for business investment and union (dis)organization likely has spillover effects beyond state borders, weak unions in one state may affect union organization in other states. We examine how union decline in one state is associated with union decline in neighboring states, and whether the presence of prounion (left-leaning) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Recent work has demonstrated the horizontal mobilization of organized interests, as sub-national policies shape the capacities of groups to influence policy in other federal units (Darmofal et al 2019;Finger and Hartney 2019;Trachtman 2020b). Related research has explored the vertical mobilization of city governments that lobby directly in national and state politics (Goldstein and You 2017;Darmofal et al 2019;Payson 2020). This paper extends our understanding of the vertical mobilization of interest groups by specifying mechanisms by which state policy and politics can influence the preferences of business interests at the national level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has demonstrated the horizontal mobilization of organized interests, as sub-national policies shape the capacities of groups to influence policy in other federal units (Darmofal et al 2019;Finger and Hartney 2019;Trachtman 2020b). Related research has explored the vertical mobilization of city governments that lobby directly in national and state politics (Goldstein and You 2017;Darmofal et al 2019;Payson 2020). This paper extends our understanding of the vertical mobilization of interest groups by specifying mechanisms by which state policy and politics can influence the preferences of business interests at the national level.…”
Section: Discussionmentioning
confidence: 99%
“…This includes in particular cross-level effects on organized interests which are central to modern political life. Some recent research has begun to pay greater attention to these effects, in particular with regard to unions and cities (Goldstein and You 2017;Darmofal et al 2019). In the following, we focus on firms, whose political clout is significant in policy-making (Gilens and Page 2014).…”
Section: Firms and Federalismmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes in particular cross-level effects on organized interests which are central to modern political life. Some recent research has begun to pay greater attention to these effects, in particular with regard to unions and city governments (Goldstein and You 2017;Darmofal et al 2019). In the following, we focus on firms, whose political clout is significant in policy-making.…”
Section: Firms and Federalismmentioning
confidence: 99%
“…Our argument on a home state effect speaks to recent work on the role of organized interests in mediating interdependencies across sites and levels of government in American federalism. This work has shown that sub-national governments engage in national politics (Goldstein and You 2017;Darmofal et al 2019;Payson 2020;Karch and Rose 2019), and that policies adopted in one state can affect the ability of interest groups to engage politically in other states (Darmofal et al 2019;Finger and Hartney 2019;Trachtman 2020b). We extend this line of research by highlighting the ways sub-national governments can also influence business preferences in the national politics.…”
Section: Introductionmentioning
confidence: 99%